Interaction Between the Intestinal Microbial Community and Transcriptome Profile in Common Carp (Cyprinus carpio L.) - Su, Shengyan; Jing, Xiaojun; Zhang, Chengfeng; Hou, Yiran; Li, Zhixun; Yang, Xingli; Zhou, Xiaolin; Xu, Pao; Tang, Yongkai; Zhu, Jian (Frontiers in Microbiology, 2021)
In a previous study, we found that the growth performance of the new strain of Huanghe carp is related to gene expression and bacterial community in the gut. In order to better understand the relationship between the gene expression level and bacterial abundance in the gut, we studied the growth performance, gut bacterial structure, and transcriptome profile in the 4th generation of the new carp strain (selection group) at harvesting time, and compared them with the control line (traditional Huanghe carp). Body weight, depth, width, and length increased 14.58%, 7.14%, 5.04%, and 5.07% respectively. The gut microbiome of the selection group also exhibited significantly higher species diversity parameters (Shannon, Simpson, and chao1). Both PCA and phylogenetic analyses divided all gut samples into two parts: control and selection group. Aeromonas was the dominant taxon in the control group, followed by Firmicutes and Roseomonas; in the selection group, Roseomonas was the dominant taxon, followed by Firmicutes and then Aeromonas. Among the 249 significantly differentially expressed genes, 194 were downregulated and 55 were upregulated. Functional GO annotation produced 13 terms in the biological process, 8 in the cellular component, and 7 in the molecular function categories. KEGG annotation indicated that most of these genes were associated with the immune-related pathways. A total of 2,892 pairs of genes (245) and baceterial genera (256) were analysed using Pearson’s correlation analysis. Most of the identified associations were mapped to the immune system, bacterial community, and cell differentiation categories. The top-10 bacterial genera identified by these analyses were Methylocystis, Ohtaekwangia, Roseomonas, Shewanella, Lutispora, GpⅥ, Desulfovibrio, Candidatus_Berkiella, Bordetella, and Azorhizobium. Genes paired with bacteria flora were divided into 4 functional categories: immune, growth, adipocyte differentiation, and nerve regulation. These genes may be related to the comparatively fast growth and high muscle polyunsaturated fatty acid content of the Huanghe carp new strain. Meanwhile, nerve regulation-related genes may be a reflection of the microbiota-gut-brain axis. These results illustrate that gut bacterial community structure is associated with the growth performance and gene expression in the Huanghe carp new strain.